2010
DOI: 10.1021/tx100337s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on a P450-Mediated Rearrangement of BMS-690514: Conversion of a Pyrrolotriazine to a Hydroxypyridotriazine

Abstract: BMS-690514 ((3R,4R)-4-amino-1-((4-((3-methoxyphenyl)amino)pyrrolo[2,1-f][1,2,4] triazin-5-yl)methyl)-3-piperidinol) is an oral oncologic agent being developed for the treatment of patients with advanced nonsmall cell lung cancer and breast cancer. The compound is metabolized via multiple metabolic pathways, including P450-mediated oxidation at one of the carbons of its pyrrolotriazine group. Oxidation at this site results in the formation of two metabolites, M1 and M37. Mass spectrometric and NMR analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The reaction is rationalized by an electrophilic attack of a P450 (CYP3A4?) on a pyrrole ring to form a hydroxypyrrole, which rearranges to open the pyrrole ring and eventually involves reaction of a neighboring aniline ring to form a stable carbinolamine product (21).…”
Section: Oxidationsmentioning
confidence: 99%
“…The reaction is rationalized by an electrophilic attack of a P450 (CYP3A4?) on a pyrrole ring to form a hydroxypyrrole, which rearranges to open the pyrrole ring and eventually involves reaction of a neighboring aniline ring to form a stable carbinolamine product (21).…”
Section: Oxidationsmentioning
confidence: 99%
“…M2, M37, and M3 were minor oxidative metabolites in the HLM incubation. Under the chromatographic conditions used in this study, M2 and M37 (hydroxylated metabolites) coeluted (Hong et al, 2011), and together they accounted for 0.4% of the sample radioactivity. Metabolite M3 (an O-demethylated metabolite) accounted for 1.9% of the radioactivity.…”
Section: Incubations Of [mentioning
confidence: 76%
“…The flux through the M1 pathway could not be determined from the human absorption, distribution, metabolism, and excretion (ADME) study because M1 was thermally labile and decomposed into multiple unknown degradation products. It is likely that M1 did not survive in the gastrointestinal tract or was unstable during collection and processing of urine, bile, and fecal samples Hong et al, 2011). However, in vitro studies in human liver microsomes and in vivo human plasma profiles indicated that the flux through M1 could be significant Hong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples of cyclized metabolites are aminals, where the cyclized metabolite is formed from an aldehyde intermediate. A recent example is the inhibitor of the human epidermal growth factor BMS-690514 14, where a substituted pyrrolo[2,1-f][1,2,4]triazine ring is opened and the aldehyde formed binds to a different, more nucleophilic, nitrogen in the molecule with ring closure (Hong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%